Pengaruh Media Sosial Terhadap Praktik Sharenting Yang Berujung Eksploitasi Pada Anak (Jurnal ENTITAS SOSIOLOGI, 2023)
The practice of sharenting is a combination of oversharing and parenting which is defined as an action taken by parents in sharing their child's parenting patterns and activities on social media. Unknowingly, the practice of sharing on social media can lead to exploitation of children. The method used in this research is quantitative. The sampling technique used accidental sampling technique. Data was collected through an online questionnaire and the number of representative samples was 55 teenagers who were around the area of the Indonesian Education University, Bandung City, West Java. Data testing uses data validity tests, reliability tests, normality tests and linearity tests. Data processing was carried out using Microsoft Excel and using descriptive statistical methods. The results of the hypothesis show that social media can affect the practice of sharenting. The conclusion from this study is that the factors that can lead to sharenting practices are social media which has an effect of 12.5% or 0.125, the rest can be influenced by other factors such as parents' lack of digital literacy, not understanding what sharenting is and feeling that privacy and the child's rights fully belong to the parents.